If the earl only knew - Forester, Amanda (Sourcebooks Casablanca, 2016)
Orphaned at a young age, Lady Katherine Ashton and her brother have spent most of their lives on the high seas, seeking to restore their family fortune through somewhat dubious means. After that kind of adventure, Kate knows she won't ever be accepted as a proper society lady. To the annoyingly clever, temptingly handsome, and altogether troublesome Earl of Wynbrook, society ladies are a dead bore. Kate, on the other hand, is scandalous, alluring, and altogether fascinating. And Kate can't decide which she relishes more, the thrill of chasing fearsome pirates, or having Wynbrook chase after her...